Establishing a biologics service for patients with inflammatory bowel disease. Issue 3 (21st April 2011) - Hamlin, P J; Warren, L; Everett, S M
Abstract : The use of anti-TNF therapy in the management of Crohn's disease and, to a lesser extent ulcerative colitis, is increasing. This article aims to discuss the practicalities of establishing a biologics service for patients with inflammatory bowel disease. Current guidelines on the use of these drugs are reviewed followed by a discussion on the choice of which anti-TNF agent to use based on costs and patient choice. A model for the initiation, administration, monitoring and assessment of patients receiving anti-TNF therapy is proposed. The need for a national biologics registry is highlighted in the summary.